A novel potential therapy for vascular diseases: blood‐derived stem/progenitor cells specifically activated by dendritic cells. Issue 7 (October 2014) - Porat, Yael; Assa‐Kunik, Efrat; Belkin, Michael; Krakovsky, Michael; Lamensdorf, Itschak; Duvdevani, Revital; Sivak, Galit; Niven, Mark J.; Bulvik, Shlomo
Abstract Background Vascular diseases are a major cause of morbidity and mortality, particularly in diabetic patients. Stem/progenitor cell treatments with bone marrow‐derived cells show safety and promising outcomes, albeit not without some preprocedural adverse events related to cell collection and mobilization. We describe a novel technology for generating a therapeutic population (BGC101) of enriched endothelial progenitor cells (EPCs) from non‐mobilized blood, using dendritic cells to specifically direct stem/progenitor cell activity in vitro. Methods and results Selected immature plasmacytoid and myeloid dendritic cells from 24 healthy and two diabetic donors were activated with anti‐inflammatory and pro‐angiogenic molecules to induce specific activation signals. Co‐culturing of activated dendritic cells with stem/progenitor cells for 12–66 h generated 83.7 ± 7.4 × 106 BGC101 cells with 97% viability from 250 mL of blood. BGC101, comprising 52.4 ± 2.5% EPCs (expressing Ulex‐lectin, AcLDL uptake, Tie2, vascular endothelial growth factor receptor 1 and 2, and CD31), 16.1 ± 1.9% stem/progenitor cells (expressing CD34 and CD184) and residual B and T helper cells, demonstrated angiogenic and stemness potential and secretion of interleukin‐8, interleukin‐10, vascular endothelial growth factor and osteopontin. When administered to immunodeficient mice with limb ischemia (n = 40), BGC101 yielded a high safety profile and significantly increased blood perfusion, capillary density and leg function after 21 days. Cell tracking and biodistribution showed that engraftment was restricted to the ischemic leg. Conclusions These observations provide preliminary evidence that alternatively activated dendritic cells can promote the generation of EPC‐enriched stem/progenitor cells within a 1‐day culture. The resulting product BGC101 has the potential for treatment of various vascular conditions such as coronary heart disease, stroke and peripheral ischemia. Copyright © 2014 John Wiley & Sons, Ltd.